A comparative study of registration practices in selected organ works of Johann Sebastian Bach (1685-1750) based on recordings made by Marie-Claire Alain and Jacques van Oortmerssen - Viljoen, Wim (University of Pretoria, 2013)
Dissertation (M Mus (Performing Art))--University of Pretoria, 2008.